2006
DOI: 10.1037/0022-3514.91.4.730
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resilience, positive emotions, and successful adaptation to stress in later life.

Abstract: In 3 studies, the authors investigated the functional role of psychological resilience and positive emotions in the stress process. Studies 1a and 1b explored naturally occurring daily stressors. Study 2 examined data from a sample of recently bereaved widows. Across studies, multilevel random coefficient modeling analyses revealed that the occurrence of daily positive emotions serves to moderate stress reactivity and mediate stress recovery. Findings also indicated that differences in psychological resilience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

78
853
5
43

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,206 publications
(979 citation statements)
references
References 168 publications
78
853
5
43
Order By: Relevance
“…It was suggested that because positive emotions can increase resilience, positive emotions allow persons to develop resources that help them deal with life challenges that in turn lead to life satisfaction (Cohn, Fredrickson, Brown, Mikels, & Conway, 2009). Research supports the claim that psychological resilience is associated with positive emotions especially during stressful times (e.g., Ong, Bergeman, Bisconti, & Wallace, 2006). Similar findings were reported with enduring relationships such as marriages.…”
supporting
confidence: 75%
“…It was suggested that because positive emotions can increase resilience, positive emotions allow persons to develop resources that help them deal with life challenges that in turn lead to life satisfaction (Cohn, Fredrickson, Brown, Mikels, & Conway, 2009). Research supports the claim that psychological resilience is associated with positive emotions especially during stressful times (e.g., Ong, Bergeman, Bisconti, & Wallace, 2006). Similar findings were reported with enduring relationships such as marriages.…”
supporting
confidence: 75%
“…Positive affect has been proposed as an adaptational mechanism which may protect against the negative effects of stress on health (Folkman & Moskowitz, 2000;Ong, Bergeman, Bisconti, & Wallace, 2006). Ong and colleagues suggest that the ability to maintain positive emotions in the face of stress is one pathway through which people can successfully adapt to stress and experience better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Together these criticisms have cast doubt on the utility of resilience as a theoretical construct. For example, some researchers have investigated resilience (or ‗resiliency') as an individual trait (Ong, Bergeman, Bisconti, & Wallace, 2006) or an epiphenomenon of adaptive temperament (Wachs, 2006). In some studies (Fredrickson, Tugade, Waugh, & Larkin, 2003) habitual effective coping as a durable personal resource is considered to constitute a facet of trait resilience, which functions as a reserve that can be drawn on as a buffer against a wide range of future adversities.…”
Section: Current Conceptualisations Of Resiliencementioning
confidence: 99%
“…The promotion approach ( Figure 2): Some researchers have associated the concept of resilience with promotion of mental health (Ong et al, 2006;Patel & Goodman, 2007). This approach focuses on the development of additional resources, which can be used (applied for) by harmreduction and protection mechanisms (analogous to pre-immunization or a general strengthening of the immune system), but has been mainly associated with high individual levels of positive experience (Fredrickson, 2004;Fredrickson & Joiner, 2002).…”
Section: Resilience Approaches In Mental Health Researchmentioning
confidence: 99%
See 1 more Smart Citation